ANALISIS STRATEGI KAMPANYE POLITIK @SADULURNISYAAHMAD UNTUK PEMENANGAN DPRD PROVINSI JAWA BARAT 2024 - Ghofur, Abdul; Ayu, Rahma Syakira; Pratiwi, Amalia; Dewi, Ananda; Putri, Nayla Febrina; Nabila, Adinda (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study analyzes the political campaign carried out by @sadulurnisyaahmad on Instagram as a strategy to win the 2024 West Java Provincial DPRD Legislative Election. This study aims to determine the extent to which the digital strategy implemented is able to build self-image and strengthen the electability of legislative candidates amidst increasingly competitive political competition. The research method used is descriptive qualitative analysis with a case study approach, focusing on content, interactions, and communication patterns built through the Instagram account. The results of the study show that @sadulurnisyaahmad uses Instagram as the main media to build self-image, convey vision and mission, and strengthen closeness with voters. The strategies implemented include the use of attractive visuals, personal narratives, utilization of Instagram Stories, Reels and Live features. In addition, collaboration with local artists and the use of special hashtags also expanded the reach of the campaign.